وسائل الاتصال الحديثة وأثرها على أحكام العلاقة بين الجنسين في الفقه الإسلامي - ببوش, محمد العربي (Universty of Eloued جامعة الشهيد حمة لخضرالوادي, 2019)
الملخص: موضوع الرسالة موسوم بــ: "وسائل الاتصال الحديثة وأثرها على أحكام العلاقة بين الجنسين في الفقه الإسلامي"، وإشكاليته الرئيسة تبحث في مدى تأثر أحكام العلاقة بين الجنسين بالخصائص والأساليب التي توفرها وسائل الاتصال الحديثة في المجالات المختلفة؛ ما ارتبط منها بالعلاقات الاجتماعية أو بالمعاملات المالية. وقد جاء الموضوع في بابين: الباب الأول خُصِّصَ لتصوير ماهية وسائل الاتصال الحديثة، وانتظم في ثلاثة فصول: أولها اهتم بتعريف وسائل الاتصال الحديثة, وبيان مميزاتها, وأهم أنواعها، ودراسة أشهر نماذجها، وثانيها بَيَّنَ أساليب التواصل عبرها، وثالثها تَعَرَّضَ إلى تحدي الخصوصية فيها. أما الباب الثاني فخُصِّصَ لتجلية أثر وسائل الاتصال الحديثة على أحكام العلاقة بين الجنسين في الفقه الإسلامي, وقُسِّمَ إلى ثلاثة فصول: أولها عُني بتحديد الضوابط العامة الحاكمة للتواصل بين الجنسين عبر وسائل الاتصال الحديثة في الفقه الإسلامي, وثانيها وضح أثر وسائل الاتصال الحديثة على أحكام الأسرة من خلال مسائل في الخطبة والزواج والطلاق عبرها، وثالثها: أظهر أثرها على أحكام العلاقة بين الجنسين في المعاملات المالية والتعليم والصداقة. ومن النتائج الأساسية التي وصل إليها البحث أنَّ لوسائل الاتصال الحديثة عظيم الأثر في أحكام العلاقة بين الجنسين في شتى المجالات؛ من حيث تجديد الضوابط وتغيير بعض الأحكام والتأكيد على بعضها الآخر،كما أوصت الدراسة بضرورة الاهتمام بفقه مواقع التواصل الاجتماعي تدريسا وتأليفا، واعتماد المتصدرين للإفتاء بشأنه منهجا وسطيا يقدس النصوص الشرعية, ويراعي في تنزيلها خصائص هذه المواقع وأبعادها ومخاطرها, ومقاصد الشريعة وقواعدها. Résumé : فرنسية أو انجلزية The topic of the thesis is entitled "Modern Means of Communication and their Impact on the Relationship between two genders in Islamic Jurisprudence". The main question of this research studies the extent to which the rules of the relationship between the sexes are affected by the characteristics and methods provided by the modern means of communication in different fields, those related to social relationships or financial transactions. The thesis is composed of two chapters. The first one is devoted to depict the essence of modern means of communication. This chapter, in turn, is divided into three sub-divisions. The first is concerned with the definition of the modern means of communication, their characteristics, most important types and studying their most famous models. The second sub-division shows the forms of communication used in these means of communication. The third sub-divisions tackles the challenge of privacy in these communication means. The second chapter of the thesis clarifies the impact of modern means of communication on the rules of the relationships between the two genders in Islamic jurisprudence. This chapter is also divided into three sub-divisions. The first one is concerned with identifying the general rules governing communication between the two genders through modern means of communication in Islamic jurisprudence. The second sub-division clarifies the impact of modern means of communication on family laws through discussing issues of engagement, marriage and divorce. The third sub-division shows their impact on relationship laws between the two genders in financial transactions, education and friendship. One of the main findings of this research is that the modern means of communication have a big influence on the laws of the relationship between two genders in various fields in terms of determining the controls, changing some laws and emphasizing on some others. The study also recommends the need to pay attention to the jurisprudence of social networking sites, both in terms of teaching and writing. In addition, it advises fatwa-givers to adopt an intermediate approach that sanctifies the legal texts, and takes into account the characteristics, dimensions and risks of these sites, the purposes and rules of the Sharia when making fatwa.
أطروحة دكتوراه تخصص الفقه وأصوله في العلوم الإسلامية
Keywords: مواقع التواصل الاجتماعي- الجنسين - وسائل الاتصال الحديثة - الفقه الإسلامي: social networking sites- two genders- Modern Means of Communication- Islamic Jurisprudence